A HISTORICAL SURVEY OF NIGERIA'S ECONOMIC DIPLOMACY, 1960-1985 - Salami, Olawale Bakare (Advances in Social Sciences Research Journal, 2015)
This paper examines Nigeria’s Economic Diplomacy from independence in 1960 up to the coming of Babangida’s regime in 1985. The paper discusses among other things the origin of the doctrine and how economic diplomacy as a policy had been consistently employed by successive governments since 1960. What Babangida's regime did was to give the policy a new life in the country's foreign economic relations. Drawing from its findings, the paper concludes that though the policy is not an entirely a novel idea in Nigeria foreign policy decision making process, it became an expedient element of Babangida’s foreign policy initiatives, giving the policy the desired venom for effectiveness, due to Nigeria's economic quagmire. The research was conducted using the historical research methodology which emphasised multidisciplinary approach. Both primary and secondary data were consulted in concluding the paper.